Hiatal hernia repair with transoral incisionless fundoplication versus Nissen fundoplication for gastroesophageal reflux disease: A retrospective study - Jaruvongvanich, Veeravich K.; Matar, Reem; Reisenauer, Janani; Janu, Peter; Mavrelis, Peter; Ihde, Glenn; Murray, Michael; Singh, Sneha; Kolb, Jennifer; Nguyen, Ninh T.; Thosani, Nirav; Wilson, Erik B.; Zarnegar, Rasa; Chang, Kenneth; Canto, Marcia I.; Abu Dayyeh, Barham K. (Endoscopy International Open, 2023)
Background and study aims Concomitant hiatal hernia (HH) repair with transoral incisionless fundoplication (TIF) is a therapeutic option for patients with HH > 2 cm and gastroesophageal reflux disease (GERD). Data comparing this approach with laparoscopic Nissen fundoplication (LNF) are lacking. We performed an exploratory analysis to compare these two approaches' adverse events (AEs) and clinical outcomes.Patients and methods This was a multicenter retrospective cohort study of HH repair followed by LNF versus HH repair followed by TIF in patients with GERD and moderate HH (2–5 cm). AEs were assessed using the Clavien-Dindo classification. Symptoms (heartburn/regurgitation, bloating, and dysphagia) were compared at 6 and 12 months.Results A total of 125 patients with HH repair with TIF and 70 with HH repair with LNF were compared. There was no difference in rates of discontinuing or decreasing proton pump inhibitor use, dysphagia, esophagitis, disrupted wrap, and HH recurrence between the two groups (P > 0.05). The length of hospital stay (1 day vs. 2 days), 30-day readmission rate (0 vs. 4.3 %), early AE rate (0 vs. 18.6 %), and early serious AE rate (0 vs. 4.3 %) favored TIF (all P < 0.05). The rate of new or worse than baseline bloating was lower in the TIF group at 6 months (13.8 % vs. 30.0 %, P = 0.009).Conclusions Concomitant HH repair with TIF is feasible and associated with lower early and serious AEs compared to LNF. Further comparative efficacy studies are warranted.